On Creation : Disputatae de potentia Dei, Q. 3 - Thomas, Aquinas, Saint, 1225?-1274 (Thomas Aquinas in translation., 2011)
This volume includes a new English translation of Question 3, in which Thomas takes up questions and ideas about divine and human freedom, whether or not the world is created, the problem of evil, the efficacy of creatures, and the status of the developing human embryo. It offers a comprehensive treatment of creation and the metaphysics and anthropology Thomas employs in considering the general creation of the universe and the particular creation of each human being.